2017
DOI: 10.1016/j.jconhyd.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Solute concentration at a well in non-Gaussian aquifers under constant and time-varying pumping schedule

Abstract: Our study is keyed to the analysis of the interplay between engineering factors (i.e., transient pumping rates versus less realistic but commonly analyzed uniform extraction rates) and the heterogeneous structure of the aquifer (as expressed by the probability distribution characterizing transmissivity) on contaminant transport. We explore the joint influence of diverse (a) groundwater pumping schedules (constant and variable in time) and (b) representations of the stochastic heterogeneous transmissivity ( ) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
2
5
0
Order By: Relevance
“…These results reinforce the conclusions drawn by Riva et al (2017) and Libera et al (2017), who found that manifestations of -field Sub-Gaussianity on moments/metrics associated with flow and transport tend to become virtually undetectable for ≥ 1.8.…”
Section: Monte Carlo-based Statistical Distributions Of Metrics Characterizing Transportsupporting
confidence: 90%
See 1 more Smart Citation
“…These results reinforce the conclusions drawn by Riva et al (2017) and Libera et al (2017), who found that manifestations of -field Sub-Gaussianity on moments/metrics associated with flow and transport tend to become virtually undetectable for ≥ 1.8.…”
Section: Monte Carlo-based Statistical Distributions Of Metrics Characterizing Transportsupporting
confidence: 90%
“…Riva et al (2017) present lead-order analytical flow and transport solutions in unbounded GSG log-conductivity fields under mean-uniform flow. Libera et al (2017) rely on a numerical Monte Carlo framework to analyze the joint effects of a GSG heterogeneous log-conductivity field and a temporally variable pumping rate on solute breakthrough curves (BTCs) detected at a pumping well operating in a twodimensional domain. Besides spatial dimensionality, three major limitations can be identified for the analytical study by Riva et al (2017): ( ) macrodispersion is the only transport metric analyzed, ( ) the joint impact of local dispersivity combined with the heterogeneous advection driven by is not evaluated, and ( ) output uncertainty due to finite size of the medium is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in section 1, statistics of its spatial increments have also been documented to display a behavior consistent with what we have observed here for porosity. These concepts have already been employed in the context of preliminary analytical and numerical studies of flow and transport in porous media associated with such a statistical description by Riva et al (2017) and Libera et al (2017).…”
Section: 1029/2020wr027436mentioning
confidence: 99%
“…As expected, the difference between statistics of c(x, t) obtained with diverse α values decreases as the travel time increases and as Pe decreases (see also Figure 3.b). We point out that the effect of α on the concentration breakthrough curve (BTC) in a single realization of the permeability field has been investigated in the past [46,57]. In general, the authors observed that decreasing the value of α yields (i) a delayed first time of arrival of the solute and (b) an increasing degree of asymmetry (and heavier tails) of the BTC.…”
Section: Resultsmentioning
confidence: 99%
“…To date, this modeling strategy has been successfully applied to the interpretation of main features displayed by key parameters of porous media, including log-permeability and porosity [41,27,43], whose spatial heterogeneity is typical of natural subsurface settings. It has also been employed in preliminary analytical and numerical studies of flow and transport in porous media whose log-conductivity is characterized through a GSG model [45,46].…”
Section: Introductionmentioning
confidence: 99%